Influence of shear deformations on the effective work of piezoelectric actuators under the active damping of vibrations of a rectangular plate - Karnaukhov, V.G.; Kozlov, V. I.; Karnaukhova, T.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
On the base of refined Timoshenko’ model, the influence of the shear deformations on the effectiveness of the active daming of forced resonance vibrations of the rectangular plates by the piezoelectric actuators is investigated.